Musical borrowing from Western art music to C-Pop from 1999 to 2011 / Peng Lin - Peng , Lin (2018)
This research examines musical borrowing in Chinese popular music from 1999 to 2011. Western art music, or more commonly known as classical music and its elements used in Chinese popular music of the stated period of time will be studied in terms of its music and reception. Musical borrowing of Western music is not new as past scholars had published a few articles and book such as Burkholder (1994, 2004) and Arewa (2005), however, musical borrowing of Western art music in Chinese popular song (C-Pop) is still new in the field. The objectives of this study are to investigate in what way employed classical music element characteristics in pop songs, and to analyze music elements representing pop songs and its reception. This study is based on a qualitative research theoretical framework and methods include literature review, score analysis, lyrics analysis, listening analysis and video analysis. Selected songs were analysed as a case study where the outcome reveals the musical elements, extra-musical elements and how Western classical music was used form new musical style and as a strategy for gaining popularity and reception.